EARLY RESPONSE TO DEHYDRATION 7 Remodels Cell Membrane Lipid Composition During Cold Stress in Arabidopsis - de Dios Barajas-Lopez Juan; Tiwari Arjun; Zarza Xavier; Shaw Molly W; Pascual Jesús; Punkkinen Matleena; Bakowska Joanna C; Munnik Teun; Fujii Hiroaki (Oxford University Press, 2022)
Plants adjust to unfavorable conditions by altering physiological activities such as gene expression. Although previous studies have identified multiple stress-induced genes, the function of many genes during the stress responses remains unclear. Expression of ERD7 (Early Response to Dehydration 7) is induced in response to dehydration. Here, we show that ERD7 plays essential roles in both plant stress responses and development. In Arabidopsis, ERD7 protein accumulated under various stress conditions including exposure to low temperature. A triple mutant of Arabidopsis lacking ERD7 and two closely-related homologs had an embryonic lethal phenotype, whereas a mutant lacking the two homologs and one ERD7 allele had relatively round leaves, indicating that the ERD7 gene family has essential roles in development. Moreover, the importance of the ERD7 family in stress responses was evidenced by the susceptibility of the mutant lines to cold stress. ERD7 protein was found to bind to several, but not all, negatively charged phospholipids, and was associated with membranes. Lipid components and cold-induced reduction of PIP2 in the mutant line were altered relative to wild type. Furthermore, membranes from the mutant line had reduced fluidity. Taken together, ERD7 and its homologs are important for plant stress responses and development and associated with modification of membrane lipid composition.